Bleeding After Free Flap-Based Breast Reconstruction: A NSQIP Analysis - Orr, Jonah Parker; Shammas, Ronnie Labib; Thomas, Analise B.; Truong, Tracy; Cho, Eugenia H.; Kuchibhatla, Maragatha; Hollenbeck, Scott Thomas (Journal of Reconstructive Microsurgery, 2019)
Background Despite limited oncologic benefit for women without an increased risk for breast cancer, the rates of contralateral prophylactic mastectomy (CPM) have increased. Patients undergoing CPM are more likely to undergo bilateral and immediate breast reconstruction. This study assessed the relationship between the timing and laterality of free flap-based breast reconstruction and the risk of postoperative bleeding complications.Methods Women undergoing postmastectomy free-flap based breast reconstruction from 2010 to 2015 were identified using the National Surgical Quality Improvement Program (NSQIP) dataset. Patients were categorized according to reconstructive laterality and timing. Modified Poisson regression was used to assess the risk of postoperative bleeding and complications across reconstructive procedures.Results Of the 4,133 patients undergoing free flap-based breast reconstruction, 12% (n = 494) experienced postoperative bleeding complications. Bilateral immediate reconstruction was associated with the highest incidence of bleeding (16.6%, n = 188), followed by bilateral delayed (12.8%, n = 58), unilateral immediate (10%, n = 142), and unilateral delayed reconstruction (9.4%, n = 106). Among patients undergoing immediate reconstruction, bilateral, rather than unilateral, reconstruction was associated with a significantly elevated risk of bleeding complications (RR [rate ratio]  = 1.58; 95% CI [confidence interval] =1.19, 2.10; p = 0.0002). Furthermore, immediate bilateral reconstruction was associated with a significantly higher rate of return to the operating room (RR =1.39; 95% CI =1.06, 1.82; adjusted p = 0.009) when compared with a unilateral procedure.Conclusion Patients undergoing immediate bilateral free flap-based breast reconstruction may be at an increased risk for experiencing acute postoperative bleeding complications and a return to the operating room. Patients undergoing CPM and considering immediate reconstruction should be counseled regarding the increased morbidity of a bilateral reconstructive procedure.
Keywords: postoperative complications; bleeding; free flap; plastic surgery; breast reconstruction; contralateral prophylactic mastectomy